2007
DOI: 10.1002/ajmg.a.31668
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GJB2, GJB6, and mitochondrial DNA are rare in African American and Caribbean Hispanic individuals with hearing impairment

Abstract: Autosomal recessive nonsyndromic sensorineural hearing impairment (ARNSHI) comprises 80% of familial hearing loss cases. Approximately half result from mutations in the connexin 26 (Cx26) gene, GJB2, in Caucasian populations. Heterozygous mutations in GJB2 occasionally co-occur with a deletion of part of GJB6 (connexin 30; Cx30). It is estimated that approximately 1% of deafness is maternally inherited, due to mutations in mitochondrial DNA (mtDNA). Few studies have focused on the frequency of mutations in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 34 publications
3
47
1
Order By: Relevance
“…As in previous studies in Africans, [17] African Americans and Caribbean Hispanics with GJB6 mutations, [19] we did not find either the GJB6-D13S1830 deletion or coding region changes. Similarly, no pathogenic variants were detected in GJA1, suggesting their nonimplication in hearing loss among the Cameroonians and black South Africans studied, [15] as has been reported in African Americans.…”
Section: Gj Proteins (Connexins) and The Inner Ear A: Connexins Fosupporting
confidence: 85%
See 2 more Smart Citations
“…As in previous studies in Africans, [17] African Americans and Caribbean Hispanics with GJB6 mutations, [19] we did not find either the GJB6-D13S1830 deletion or coding region changes. Similarly, no pathogenic variants were detected in GJA1, suggesting their nonimplication in hearing loss among the Cameroonians and black South Africans studied, [15] as has been reported in African Americans.…”
Section: Gj Proteins (Connexins) and The Inner Ear A: Connexins Fosupporting
confidence: 85%
“…[24] Funding. 19 and ** Pandya et al 20 indicate that the mutation was found neither in patients nor in controls.…”
Section: Clinical Implications and Research Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Africans, Caribbean Hispanics, probably due to their African ancestry, do not show a large contribution to deafness from GJB2 variations (Samanich et al, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…The p.Val27Ile polymorphism seems to be rare or absent in European and African populations [26,32]. The second most frequent polymorphism of GJB2 is p.Glu114Gly; it occurs almost exclusively in the Asian continent (in the same regions as p.Val27Ile) and its highest AFs are found in East Asia: Koreans and Chinese 17% [13,14,18] and Japanese 13% [12] followed by Mongolians and Altaian ethnic group 11% in Central Asia [15,16].…”
Section: Introductionmentioning
confidence: 98%